HMG-boxes, ribosomopathies and neurodegenerative disease - Moss, Tom; LeDoux, Mark S.; Crane-Robinson, Colyn (Frontiers in Genetics, 2023)
The UBTF E210K neuroregression syndrome is a predominantly neurological disorder caused by recurrent de novo dominant variants in Upstream Binding Factor, that is, essential for transcription of the ribosomal RNA genes. This unusual form of ribosomopathy is characterized by a slow decline in cognition, behavior, and sensorimotor functioning during the critical period of development. UBTF (or UBF) is a multi-HMGB-box protein that acts both as an epigenetic factor to establish “open” chromatin on the ribosomal genes and as a basal transcription factor in their RNA Polymerase I transcription. Here we review the possible mechanistic connections between the UBTF variants, ribosomal RNA gene transcription and the neuroregression syndrome, and suggest that DNA topology may play an important role.